Non-Bosonic Damping of Spin Waves in van der Waals Ferromagnetic Monolayers - Michael G. Cottam; Bushra Hussain (Nanomaterials)
The spin wave renormalization processes in two-dimensional van der Waals ferromagnetic monolayers are investigated using an established non-bosonic diagram technique based on the drone-fermion perturbation method. The aim is to evaluate the damping of the long-wavelength spin wave modes at temperatures below the Curie temperature. In addition to the multi-magnon scattering processes, which typically dominate at low temperatures, an additional mechanism is found here that becomes important at elevated temperatures. This spin disorder damping mechanism, which was mainly studied previously in bulk magnetic materials and thicker films, features a spin wave or magnon being scattered by the magnetic disorder that is present when a longitudinal spin component undergoes large thermal fluctuations. The magnetic ordering in the monolayers is stabilized by an out-of-plane single-ion or Ising-type anisotropy, which influences the damping properties. Numerical results are derived for monolayer films of the van der Waals ferromagnet Cr2Ge2Te6.